2013
DOI: 10.1590/s1677-5538.ibju.2013.05.13
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of intracorporeal lithotripsy of upper tract stones is not affected by BMI and skin-to-stone distance (SSD) in obese and morbid patients

Abstract: Purpose: The purpose of this study is to determine if body mass index (BMI) and stone skin distance (SSD) affect stone free rate (SFR) in obese and morbid obese patients who underwent flexible URS for proximal ureteral or renal stones < 20 mm. Materials and Methods: A retrospective chart review was performed of consecutive patients that underwent flexible URS. Inclusion criteria were: proximal ureteral stones and renal stones less than 20 mm in the preoperative computed tomography (CT). SFR were then compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Pareek et al [15] found that both BMI and HU are independent predictors for successful SEWL. However, in respect to our findings, Dede et al [13], Bulent et al [14] and Pompeo et al [16] reported in different studies that BMI does not affect SFR. Moreover, Bulent et al [14] and Pareek et al [15] found a significant relationship between the SSD and the success of ESWL.…”
Section: Discussionsupporting
confidence: 53%
“…Pareek et al [15] found that both BMI and HU are independent predictors for successful SEWL. However, in respect to our findings, Dede et al [13], Bulent et al [14] and Pompeo et al [16] reported in different studies that BMI does not affect SFR. Moreover, Bulent et al [14] and Pareek et al [15] found a significant relationship between the SSD and the success of ESWL.…”
Section: Discussionsupporting
confidence: 53%
“…11,12 Furthermore, SSD and the Hounsfield units predict the outcomes from shock wave lithotripsy, [22][23][24] but SSD has no effect on the SF rate associated with fURS. 25 Our results suggest that SSD is not a major factor that requires the creation of appropriate access tracts and that a Swiss LithoClast pneumatic lithotripter has enough power to fragment the stones, even if the stone density is high. According to Guy's stone score, a history of spinal injury and an abnormal intrarenal anatomy are risk factors associated with PCNL outcomes.…”
Section: Commentmentioning
confidence: 67%
“…BMI is also used as predictor, which is related indirectly to the SSD, which reflects the SW path in the body, since BMI may not directly reflect central body fat distribution, it cannot reliably used as surrogate marker for SSD, the utility of BMI in predicting successful is variable, Pareek et al .,[ 4 ] demonstrates that BMI independently predict SWL outcome, they suggest that patient with BMI >30 kg/m 2 would be suitable treated by endoscopic manipulation, Yang and colleague[ 20 ] demonstrates similar results which BMI and buttock circumference being noted as predictors of SWL failure, conversely our study corroborates with recent studies that BMI is not predictive factor for SWL outcome. [ 5 21 ]…”
Section: Discussionmentioning
confidence: 99%